THE QUALITY OF QUAIL (COTURNIX-COTURNIX JAPONICA) EGG GIVEN MORINGA LEAF SOLUTION (MORINGA OLEIFERA L) - Paryanta, Paryanta; Sudrajat, Deden; Anggraeni, Anggraeni (Jurnal Peternakan Nusantara, 2019)
Egg quality can be determined by measuring exterior quality includes egg shape, weight, while interior includes haugh unit (HU) value, yolk and egg albumen. This research aims to assess the potential of moringa leaf solution as an effort to improve the quality of quail eggs. This research was conducted from December 2017 to January 2018. The research was conducted at Badrupuyuh Farm Kp. Sukajaya RT 01/02 Ciomas Bogor Regency. The livestock that used in this research are 100 quails with age 35 day and average weight 125,93 ± 3,056 g. The feed that been used is a layered commercial and drinking water that mixed with Moringa leaf solution. The research design that been used was Completely Randomized Design (RAL) with 4 treatments and 5 replications. Treatment given in this research is R0: Drinking water without Moringa leaf, R1: 5% of moringa leaf solution, R2: 10% of moringa leaf solution, R3: 15% of moringa leaf solution. The data obtained were analyzed using Analysis of Variance (ANOVA). If it shows significant difference (P <0.05) or very significant different (P <0.01) then we will test it again with Duncan test. The variables observed in this study are egg index, weight of shell, thick of shell, yolk color and haugh unit. The application of moringa leaves solution up to 10% can increase the quail egg yolk color but has no significant effect on the egg index, the weight of the shell, the thickness of the shell and the haugh unit.Keywords: egg quality, quail, Moringa leaf solution